Study of dynamic processes in bulk material during its baking - Nizhegorodov, A.I.; Gavrilin, A.N.; Moyzes, B.B.; Kuvshinov, K.A. (KU publ., 2020)
The article presents the results of research on the dynamics of the base plate of an electric furnace for the heat treatment of bulk materials. The base plate with moving trolley on elastic bonds serves as the base which transports the heat-treated material in the hot part of the heating system with a specified speed and processing time. The experimental total elastic characteristic of the oscillating system is obtained; the amplitude-frequency characteristic is constructed, which characteristic is weak nonlinearity. Experiments have shown that conical springs of different designs do not provide a strong asymmetry in the base plate oscillations and therefore the vibrational transport efficiency is weak in the horizontal position of the prototype furnace. Further experiments were conducted when the furnace was installed at an angle to the horizontal surface. The vibrational transport time of vermiculite was reached 2.7...3.2 s, depending on the excitation frequency settings near the resonance zone. It is shown that the operation of the vibrating base plate may not be stable due to the high sensitivity of the excitation frequency from various factors. Methods for reducing the sensitivity coefficient are considered.
Күйдіру кезіндегісусымалы материалдағы динамикалық процестерді зерттеу.
Исследование динамических процессов в сыпучем материале при его обжиге.
Keywords: bulk materials; electric furnace; vibrating base plate; oscillating system; nonlinear amplitudefrequency characteristic; oscillating system sensitivity to external factors